Comparative Policy Analysis of Photovoltaic Industry Development: Case Studies of China and the United States - Huang, Xin (Transactions on Economics, Business and Management Research, 2024)
Amidst the challenges in achieving the Paris Agreement objectives, the 28th Conference of the Parties (COP28) has injected renewed impetus, with the photovoltaic (PV) industry assuming a pivotal role. China and the United States, as major players in the global solar PV sector, have tailored policies reflecting the current status of their PV industries. Notably, China has transitioned from a government-led to a market-oriented approach, while the United States has pursued localization and trade protectionism strategies. This paper initiates with an overview of the PV industry policies of both countries, followed by a comparative analysis of their similarities and differences. Employing a comparative method seeks to unveil the geopolitical factors implicit in these policies, hindering cooperation between the two nations. Despite these challenges, the analysis also underscores the significant potential for collaboration in global environmental governance. In addition to highlighting the barriers to cooperation, the study aims to provide insights into opportunities for enhanced collaboration between China and the United States. By fostering cooperation, these nations can collectively address the pressing challenges posed by climate change and contribute to the realization of the Paris Agreement goals.